Pro-poor Institutions: Creating Exclusive Rights to the Poor Groups in Community Forest Management - Bhattarai, Sushma; Jha, Prakash Kumar; Chapagain, Niraj (Journal of Forest and Livelihood, 2009)
In spite of the widely accepted success of Community Forestry in reviving degraded land, it is still seen as being unable to provide tangible benefits to the poor. This paper illustrates that through continuous sharing, deliberation and negotiation among the poor and non?poor members of Community Forest User Groups (CFUGs), management of community forests can be made far more equitable than the usual scenario. Drawing from the experience on the processes and outcomes of Livelihoods and Forestry Programme (LFP), this paper brings empirical evidence of how facilitation support has enabled the poor to have more equitable access to community forests. Three key pro?poor institutional arrangements resulting from the facilitation process include: a) establishing special use rights arrangements within CFUGs for the poor, b) pro?poor silvicultural practices, and c) equitable forest product and benefit distribution mechanisms. The paper suggests some changes in policy and practice to institutionalise these outcomes. Full text is available at the ForestAction website DOI: http://dx.doi.org/10.3126/jfl.v8i2.2304 Journal of Forest and Livelihood 8(2) February 2009 pp.1-15